China-Vietnam-France relations on the verge of the collapse of the tributary system in the 19th century - Boon Dar, Ku; Luan, Vu Duong (Penerbit Universiti Kebangsaan Malaysia, 2022)
This article attempts to explain why China-Vietnam relations, which were based on tributary ties, broke down when France conquered Vietnam in the 19th century. As such, it traces the history of China-Vietnam-France relations, particularly on the eve of the French invasion of Vietnam, and explores China’s efforts to defend the country. This study is significant because it sheds light on the history of the French conquest of Vietnam while it was under the Chinese tributary system. For almost a century, China claimed to have power as a presidential state over Vietnam. However, the French did not acknowledge China’s power. Moreover, one by one, the territories of Vietnam were seized and eventually conquered by France. In this study, qualitative content analysis was applied to primary and secondary sources to evaluate the extent to which the tributary system affected and influenced the international external relations between the three countries of the three countries. The study’s findings showed that Vietnam had autonomy in theory but was submissive and willingly under China’s protection regarding its foreign affairs. However, the French did not recognize the tributary system as a foreign relationship, and they continued to mobilise colonial efforts in Vietnam in the mid-late 19th century.